METHOD AND CONTROL SET-UP OF SILICON WAFER FLATNESS - V. A. Pilipenko; A. N. Petlitsky; V. A. Gorushko; S. V. Shvedov; V. V. Ponaryadov (Приборы и методы измерений)
The method was suggested and the laser control set-up was developed of the arrow bend and bend profile of the semiconductor wafers. It was established, that on the basis of determining the inclination angle of tangent at any point of the surface due to deflection registration of the r eflected laser beam from the position, corresponding to reflection from the ideally plat surface, by means of its scanning by one of the wafer diameters it is possible to determine its bend profile.